Microtubule polymerization induced by iridium‐fullerene photosensitizers for cancer immunotherapy via dual‐reactive oxygen species regulation strategy - Xiao‐Xiao Chen; Kun Peng; Xi Chen; Zheng‐Yin Pan; Qing‐Hua Shen; Yu‐Yi Ling; Jian‐Zhang Zhao; Cai‐Ping Tan (Aggregate, 2024)
Abstract Microtubules (MTs) are key players in cell division, migration, and signaling, and they are regarded as important targets for cancer treatment. In this work, two fullerene (C60)‐functionalized Ir(III) complexes (Ir‐C601 and Ir‐C602) are rationally designed as dual reactive oxygen species (ROS) regulators and MT‐targeted Type I/II photosensitizers. In the dark, Ir‐C601 and Ir‐C602 serve as ROS scavengers to eliminate O2•− and •OH, consequently reducing the dark cytotoxicity and reversing dysfunctional T cells. Due to the efficiently populated C60‐localized intraligand triplet state, Ir‐C601 and Ir‐C602 can be excited by green light (525 nm) to produce O2•− and •OONO− (Type I) and 1O2 (Type II) to overcome tumor hypoxia. Moreover, Ir‐C601 is also able to photooxidize tubulin, consequently interfering with the cellular cytoskeleton structures, inducing immunogenic cell death and inhibiting cell proliferation and migration. Finally, Ir‐C601 exhibits promising photo‐immunotherapeutic effects both in vitro and in vivo. In all, we report here the first MT stabilizing photosensitizer performing through Type I/II photodynamic therapy pathways, which provides insights into the rational design of new photo‐immunotherapeutic agents targeting specific biomolecules.